Tomato transcriptional repressor MYB70 directly regulates ethylene‐dependent fruit ripening. (18th November 2020) - Cao, Haohao; Chen, Jing; Yue, Min; Xu, Chan; Jian, Wei; Liu, Yudong; Song, Bangqian; Gao, Yanqiang; Cheng, Yulin; Li, Zhengguo
SUMMARY: Ethylene is a key plant hormone controlling the ripening of climacteric fruits, and several transcription factors acting as important regulators of fruit ripening have been identified in tomato ( Solanum lycopersicum ), a model for climacteric fruits. The vast majority of these transcription factors are transcriptional activators, however, and the associated transcriptional regulatory mechanisms of most regulators are unclear. Here, we report on a tomato transcriptional repressor (termed SlMYB70) that negatively regulates fruit ripening by directly modulating ethylene biosynthesis. As an EAR motif‐containing MYB transcription factor‐encoding gene, SlMYB70 displayed a ripening‐associated expression pattern and was responsive to ethylene. RNA interference (RNAi)‐mediated repression of SlMYB70 accelerated fruit ripening, but overexpression of SlMYB70 delayed fruit ripening. Ethylene production was noticeably increased and decreased in SlMYB70 ‐RNAi and SlMYB70 ‐overexpressing lines, respectively, compared with wild‐type tomatoes. SlMYB70 was proven to be a transcriptional repressor, dependent on the EAR repression motif, and to repress the transcription of two ethylene biosynthesis genes in fruit ripening, namely SlACS2 and SlACO3 . The promoters of SlACS2 and SlACO3 are directly bound by SlMYB70, which was verified using a combination of yeast one‐hybrid chromatin immunoprecipitation quantitative polymerase chain reaction and electrophoretic mobility shift assays. These results suggest that SlMYB70 negatively regulates fruit ripening via the direct transcriptional repression of ethylene biosynthesis genes, which provides insights into the ethylene‐mediated key regulatory hierarchy in climacteric fruit ripening, and also highlights different types of transcriptional regulation of fruit ripening. Significance Statement: Transcription factors (TFs), which function as activators or repressors, act as key regulators of various biological processes and the majority of known fruit ripening‐related TFs are activators. Here, we report on a transcriptional repressor that is a major regulator of tomato fruit ripening by directly regulating ethylene‐mediated fruit ripening. Our findings provide novel insights into ethylenemediated key regulatory hierarchy in climacteric fruit ripening and highlight different types of transcriptional regulation of fruit ripening.